Effects of Hepatic Impairment on the Pharmacokinetics of the Dual GIP and GLP-1 Receptor Agonist Tirzepatide - Urva, Shweta; Quinlan, Tonya; Landry, John; Ma, Xiaosu; Martin, Jennifer A.; Benson, Charles T. (Clinical pharmacokinetics, 2022)
Background and Objective Tirzepatide, a novel, once-weekly, dual glucose-dependent insulinotropic polypeptide and glucagon-like peptide-1 receptor agonist, is approved in the US as a treatment for type 2 diabetes and is under development for long-term weight management, heart failure with preserved ejection fraction, and nonalcoholic steatohepatitis. This study evaluated the pharmacokinetics and tolerability of tirzepatide in participants with hepatic impairment (with or without type 2 diabetes) versus healthy participants with normal hepatic function. Methods Participants in this parallel, single-dose, open-label study were categorized by hepatic impairment defined by the baseline Child-Pugh (CP) score A (mild impairment; n = 6), B (moderate impairment; n = 6), or C (severe impairment; n = 7) or normal hepatic function ( n = 13). All participants received a single subcutaneous 5-mg dose of tirzepatide. Blood samples were collected to determine tirzepatide plasma concentrations to estimate pharmacokinetic parameters. The primary pharmacokinetic parameters of area under the drug concentration–time curve from zero to infinity (AUC 0–∞ ) and maximum observed drug concentration ( C max ) were evaluated using an analysis of covariance. The geometric least-squares means (LSM) and mean ratios for each group, between control and hepatic impairment levels, and the corresponding 90% confidence intervals (CIs) were estimated. The analysis of the time to maximum observed drug concentration was based on a nonparametric method. The relationships between the pharmacokinetic parameters and CP classification parameters (serum albumin level, total bilirubin level, and international normalized ratio) were also assessed. Adverse events were monitored to assess safety and tolerability. Results Tirzepatide exposure, based on AUC 0–∞ and C max , was similar across the control and hepatic impairment groups. Statistical analysis showed no difference in the geometric LSM AUC 0–∞ or C max between participants in the control group and the hepatic impairment groups, with the 90% CI for the ratios of geometric LSM spanning unity (AUC 0–∞ ratio of geometric LSM vs control [90% CI 1.08 [0.879, 1.32], 0.960 [0.790, 1.17], and 0.852 [0.699, 1.04] and C max ratio of geometric LSM vs control [90% CI]: 0.916 [0.726, 1.16], 1.00 [0.802, 1.25], and 0.972 [0.784, 1.21] for mild, moderate and severe hepatic impairment groups, respectively). There was no change in median time to C max of tirzepatide across all groups (time to C max median difference vs control [90% CI]: 0 [− 4.00, 12.00], 0 [− 12.00, 12.00], and 0 [− 11.83, 4.17], respectively). There was no significant relationship between the exposure of tirzepatide and the CP score ( p > 0.1 for AUC 0–∞ , C max , and apparent total body clearance). Similarly, there was no clinically relevant relationship between the exposure of tirzepatide and serum albumin level, total bilirubin level, or international normalized ratio. The geometric LSM half-life values were also similar across the control and hepatic impairment groups. No notable differences in safety profiles were observed between participants with hepatic impairment and healthy control participants. Conclusions Tirzepatide pharmacokinetics was similar in participants with varying degrees of hepatic impairment compared with healthy participants. Thus, people with hepatic impairment treated with tirzepatide may not require dose adjustments. Clinical Trial Registration ClinicalTrials.gov identifier number NCT03940742.